DETERMINATION OF TRACE ELEMENTS IN THE HAIR OF HORSES - NSSIEN, M.A.S.; OMOBA, N.A.; ONWUKA, S.K. (Nigerian Journal of Animal Science, 2023)
Hair samples from the mid sides of 18 horses were analyzed for 7 trace elements- .cobalt (CQ), copper (Cu), iron (Fe), lead (Pp.), magnesium (Mg), silicon (Si) and zinc (Zn) using atomic absorption spectrophotometer (AAS) The resulting data were compared statistically according to the age and sex of the animals-6 adults (3 males and 3 females); 6 ponies (3 males, 3 females) and 6 foals (3 males, 3 females). Fe was found to be most abundant of the elements investigated. It had an overall mean of 270.78k69.78ppm. The others followed in this order: Zn (102.87r17.92 ppm); Cu, (4.85rZ.OBppm); Mg, (0.18 0.09ppm); Co, (0.079, 0.02ppm); Pp., (0.053fl.02ppm) and Si (0.033-eO.Olppm). Analyzing the data statistically with age and sex as variables revealed significant mean differences (P<0.05) among the 3 age groups (adult, pony, foal) and sexes (male and female). While some of the elements e.g. Cu increased in value from the young (foal) to the adult, others, e.g. zinc decreased in the same direction these findings are discussed with regard to their possible implications for the management of the horse